Impact of a Simulation-Based Communication Workshop on Resident Preparedness for End-of-Life Communication in the Intensive Care Unit - Markin, Abraham (Crit Care Res Pract, 2015)
Introduction. Although residents frequently lead end-of-life (EOL) discussions in the intensive care unit (ICU), training in EOL care during residency has been required only recently, and few educational interventions target EOL communication in the ICU. This study evaluated a simulation-based intervention designed to improve resident EOL communication skills with families in the ICU. Methods. Thirty-four second-year internal medicine residents at a large urban teaching hospital participated in small group sessions with faculty trained in the “VitalTalk” method. A Likert-type scale questionnaire measured self-assessed preparedness before, immediately following, and approximately 9 months after intervention. Data were analyzed using Wilcoxon rank-sum analysis. Results. Self-assessed preparedness significantly improved for all categories surveyed (preintervention mean; postintervention mean; p value), including discussing bad news (3.3; 4.2; p < 0.01), conducting a family conference (3.1; 4.1; p < 0.01), discussing treatment options (3.2; 3.9; p < 0.01), discussing discontinuing ICU treatments (2.9; 3.5; p < 0.01), and expressing empathy (3.9; 4.5; p < 0.01). Improvement persisted at follow-up for all items except “expressing empathy.” Residents rated the educational quality highly. Conclusion. This study provides evidence that brief simulation-based interventions can produce lasting improvements in residents' confidence to discuss EOL care with family members of patients in the ICU.